Generasi Emas 2045: Peningkatan Kapabilitas Guru Pendidikan Anak Usia Dini melalui Implementasi Teknologi Artificial Intelligence - Nadia, Fiona Niska Dinda; Lestari, Yetty Dwi; Akbar, Rasyidi Faiz; Putra, Syaifurrizal Wijaya; Sholicah, Sinta Fanidatus; Ulya, Zaidatul; Amanda, Sharen Gracia (Universitas Negeri Surabaya, 2025)
Preschool teachers (kindergartens) encounter challenges in the current era of rapid technological advancement. The constraints imposed by technology-based learning methodologies have resulted in the adoption of disparate educational practices among kindergartens, thereby engendering educational disparities. Indeed, the quality of early childhood education serves as a foundational element in developing exceptional human resources (HR) who will become the nation's future leaders. In this regard, it is imperative for preschool teachers to adopt innovative learning methodologies, given their role in shaping children's cognitive, social, emotional, and linguistic development. In light of these challenges, the present Community Service initiative aims to provide a workshop focusing on variations in learning methods and teaching materials, particularly on technological and Artificial Intelligence (AI) approaches. The community service activity was conducted at Raudhatul Athfal (RA) Nizhamiyah, located in Rejoagung Village, Ploso Sub-district, Jombang Regency, East Java Province. Rejoagung Village is a community with a predominantly lower-middle-class economic profile, with a significant proportion of the workforce engaged in market and factory-related occupations. This underscores the pressing need for the implementation of this community service initiative. This community service activity could contribute to Sustainable Development Goal #4, which focuses on the quality of education. The results of this community service activity have shown an increase in the knowledge and skills of productive economic partners. RA Nizhamiyah teachers participating in the activity have been able to implement artificial intelligence (AI) to create creative and innovative teaching materials, such as interactive quizzes accompanied by visualization and audio, educational children's songs, and PowerPoint presentations. The post-training evaluation revealed that the participating teachers demonstrated a profound comprehension of creating AI-based teaching materials, with a mean score of 94.28 out of 100. Moreover, the evaluation results indicated that 91.42% of the participants expressed a strong intention to incorporate AI in creating more innovative teaching materials.